PERFORMANCE ANALYSIS OF REAL TIME STREAMING PROTOCOL (RTSP) AND REAL TIME TRANSPORT PROTOCOL (RTP) USING VLC APPLICATION ON LIVE VIDEO STREAMING - Kariyamin, Kariyamin; Riadi, Imam; Herman, Herman (Informatika, Universitas Jenderal Soedirman, 2023)
Video is a means of delivering very complete information and can be implemented using streaming technology. Networking services for local media exchange are helpful in teaching and learning activities, such as simultaneous video playback. Submission of information in the form of this video can be done by unicast, multicast or Broadcast packet delivery Live video streaming using RTP and RTSP protocol. The test was done through three experiments ie unicast, multicast and broadcast for five times. The output occurring at (RTP) is 4.73 MBit / sec for 5 client, higher than from (RTSP) of 13.799 MBit / sec for 5 client. This test occurs a very high Delay on RTP while RTSP has a low Delay in RTP. Meanwhile, the packet loss that occurs in (RTP) is 124.50% lower than (RTSP) which is 6.06% from 5 clients each. Because RTSP is an applicationlevel protocol for data delivery control that has real time characteristics such as streaming media. While RTP is designed not for streaming but to handle the actual data transmission of data in the form of sound or image or both, especially those based on real time such as streaming media.